Daytime space cooling with phase change material ceiling panels discharged using rooftop photovoltaic/thermal panels and night-time ventilation. (2nd October 2016) - Bourdakis, Eleftherios; Péan, Thibault Q.; Gennari, Luca; Olesen, Bjarne W.
Abstract : The possibility of using photovoltaic/thermal panels for producing cold water through the process of night-time radiative cooling was experimentally examined. The cold water was used to discharge phase change material in ceiling panels in a climatic chamber. Both night-time radiative cooling and night-time ventilation were used as the discharging method in five experiments, simulating summer conditions. The operative temperature remained within the range of Category III of standard DS/EN 15251 for 50% to 99% of the occupancy period. The percentage of electrical energy usage covered from the photovoltaic/thermal varied from 56% to 122%. The phase change material ceiling panels were thus, capable of providing an acceptable thermal environment and the photovoltaic/thermal panels were able to provide most of the required electricity and cold water needed for cooling.